Analyzing The Critical Factors for Humanitarian Response on Flood-Related Disaster - Puteri Fadzline, Muhamad Tamyez; Gerth, Natalie Christiane Isabella; Abdul Rahman, Zahari; Mohd Nizam, Abdul Rashid (Penerbit Universiti Malaysia Pahang, 2021)
Every year, thousands of people in Malaysia have to be moved out and be relinquished from their homes due to heavy rainfall and poor irrigation system that led to flood situation especially on monsoon season. Thus, the current study aims to concentrate on the two central aspects of disaster management in the context of flood disaster management in Kuantan, Pahang by the means of a mixed-method approach. The effectiveness of communication mechanisms in the case of floods is assessed with quantitative analysis using descriptive design. On another note, this study also takes a closer look at the underlying logistical framework found in flood disaster contexts and identifies its critical success factors via a qualitative research technique. Using thematic analysis, in-depth semi-structured interviews are analysed to arrive at conclusions regarding the critical success factors. Findings on the effectiveness of disaster communication indicated that the communication between authorities,agencies, non-government organizations and flood victims are still in need of improvement particularly related to emergency updates and increasing community awareness on the right actions for upcoming floods. The study also proved that coordination, communication, knowledge, and preparedness are the critical success factors for humanitarian response in the case of flood management. It is vital to protect the communities from flood disaster; hence, a clear and precise standard operating procedure need to bein place and must be integrated among all related agencies which will benefits the stakeholders.